The Relationship Between The 21st Century Administrative Skills And Decision Making of School administrators Under Kanchanaburi Secondary Educational Service Area Office - Manirod, Kitsanaphron; Ruamchomrat, Pongsak; Pumklom, Mitparnee (Mahachula Academic Journal, 2023)
The purpose of this research was to (1) Study 21st century administrative skills, (2) Study decision-making of administrator and (3) Study the relationship between the 21st century administrative skills and decisionmaking of school administrator under the Kanchanaburi Secondary Education Service Area Office. The sample consisted of 299 teachers in schools under Kanchanaburi Secondary educational Service area Office, selected by stratified random sampling according to classified by school sizes. A constructed 5-level rating scale questionnaire with content validity 0.67-1.00 and the reliability of 0.97 was used as a tools to collect data. The statistics employed for data analysis were percentage, mean, standard deviation, and Pearson’s product moment correlation coefficient. Statistical significance was set at 0.01 The findings were as follows. (1) The 21st century administrative skills of administrator under Kanchanaburi Secondary Educational Service Area Office overall and each aspects were at the high level, ranking from high to low : leadership and responsibility, social skills and cross-cultural skills, creativity and being yourself, flexibility and adaptability, and terms of being a creator or producing and responsible for being reliable. (2) Decision making of the schools administrators under Kanchanaburi Secondary Educational Service Area Office overall and each aspects were at the high level, ranking from high to low : problem definition, development of operational strategic plans, problem analysis, creating rules for methods, and the implementation of plans. (3) The relationship between the 21st century administrative skills and decision-making of school administrator under the Kanchanaburi Secondary Education Service Area Office, and overall were positive correlated at a highest level with a statistical significance at 0.01